Design of low-cost and high-speed portable two-dimensional electrical impedance tomography (EIT) - Aris, Widodo; ., Endarko (International Journal of Engineering and Technology, 2019)
Electrical Impedance Tomography (EIT) is a non-invasive of biomedical imaging technique that used constant electric current as a signal modality. The main proposed study was to design two-dimensional EIT system that could support high speed for detection of anomalies inside the practical phantom and has a low cost in fabrication. High-speed portable two-dimensional EIT has been successfully designed and fabricated to generate a reconstructed image from data acquisition in the practical phantom with 16 electrodes. The manufactured EIT equipped with a 7-inch screen as monitoring display, Raspberry Pi 3 Model B and Arduino Uno as controlling and processing units. The system was also used Gauss-newton method for image reconstruction that using Phyton programming which embedded into Raspberry Pi 3 Model B. The results showed that the portable EIT system produced a high-speed data acquisition and image reconstruction with a process is less than 7 seconds. The manufactured EIT revealed that the system had a potential application for medical imaging.Â Â Â